2019
DOI: 10.1111/nejo.12289
|View full text |Cite
|
Sign up to set email alerts
|

Buyer and Seller Differences in Business‐to‐Business Negotiations

Abstract: The purpose of this article is twofold: first, to examine the differences between buyers' and sellers' use of negotiation tactics in face‐to‐face business‐to‐business (B2B) negotiations and second, to explore how negotiators' professed negotiation styles influence buyers' and sellers' use of tactics. The methodology is a multiple case study analysis of eighteen negotiators representing twelve companies in six real‐life buyer–seller negotiations in B2B settings analyzed using qualitative research methods, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…This can done in a distributive and an integrative manner with, using a pie analogy, distributive negotiation focusing on dividing the pie between the participants and integrative negotiation on enlarging the pie for both. There is evidence that "buyers and sellers perceive their business-to-business (B2B) negotiations as distributive exchanges rather than opportunities for integrative bargaining and value creation" (Sigurðardóttir, Hotait, & Eichstädt, 2019) and Sigurðardóttir et al (2019) found that negotiations tactics are in most cases (too) assertive and competitive, probably due to a lack of negotiation training. This means that the distributive approach tends to prevail over the integrative one, which promotes collaborative negotiation for use in strategic business environments (Sigurðardóttir et al, 2019).…”
Section: Game 2 -Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…This can done in a distributive and an integrative manner with, using a pie analogy, distributive negotiation focusing on dividing the pie between the participants and integrative negotiation on enlarging the pie for both. There is evidence that "buyers and sellers perceive their business-to-business (B2B) negotiations as distributive exchanges rather than opportunities for integrative bargaining and value creation" (Sigurðardóttir, Hotait, & Eichstädt, 2019) and Sigurðardóttir et al (2019) found that negotiations tactics are in most cases (too) assertive and competitive, probably due to a lack of negotiation training. This means that the distributive approach tends to prevail over the integrative one, which promotes collaborative negotiation for use in strategic business environments (Sigurðardóttir et al, 2019).…”
Section: Game 2 -Negotiationmentioning
confidence: 99%
“…There is evidence that "buyers and sellers perceive their business-to-business (B2B) negotiations as distributive exchanges rather than opportunities for integrative bargaining and value creation" (Sigurðardóttir, Hotait, & Eichstädt, 2019) and Sigurðardóttir et al (2019) found that negotiations tactics are in most cases (too) assertive and competitive, probably due to a lack of negotiation training. This means that the distributive approach tends to prevail over the integrative one, which promotes collaborative negotiation for use in strategic business environments (Sigurðardóttir et al, 2019). Therefore, there are opportunities for developing training in the integrative negotiation approach, with the need to incorporate social exchange aspects, to form the basis of the learning objectives.…”
Section: Game 2 -Negotiationmentioning
confidence: 99%
“…Novel literature deals with different aspects of negotiation such as characterization of negotiation behavior (Saorín-Iborraa & Cubillo, 2019), the expectation of future negotiation interaction on bargaining processes and outcomes (Patton& Balakrishnan, 2010), and power and negotiation (Schaerer et al, 2020). However, "there is a lack of information about what actually occurs during business negotiations in general" despite the importance of the negotiation to the success of business strategies, (Fells et al 2015) and how practitioners behave in business-to-business (B2B) settings (Agndal, Age, and Frick 2017, cited in Sigurðardóttir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…After all, one-on-one negotiation involves two well-defined interaction partners, both of whom may influence the negotiation outcomes (Elfenbein et al, 2008). Negotiations are one of the most essential components in business success (Herbst and Schwarz 2011, cited in Sigurðardóttir et al, 2019). Negotiation outcomes affect the development of negotiated relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Novel literature deals with different aspects of negotiation such as characterization of negotiation behavior (Saorín-Iborraa & Cubillo, 2019), the expectation of future negotiation interaction on bargaining processes and outcomes (Patton& Balakrishnan, 2010), and power and negotiation (Schaerer et al, 2020). However, "there is a lack of information about what actually occurs during business negotiations in general" despite the importance of the negotiation to the success of business strategies, (Fells et al 2015) and how practitioners behave in business-to-business (B2B) settings (Agndal, Age, and Frick 2017, cited in Sigurðardóttir et al, 2019).…”
Section: Introductionmentioning
confidence: 99%